Atrial Fibrillation and Long QT Syndrome Presenting in a 12-Year-Old Girl. (5th November 2012) - Knoche, Jonathan W.; Orland, Kate M.; January, Craig T.; Maginot, Kathleen R.
Abstract : Atrial fibrillation (AF) is rare in the pediatric population; however, there is increasing recognition that AF can be inherited. Long QT syndrome (LQTS), likewise, can be both acquired and inherited with mutations leading to abnormalities in cardiac ion channel function. Mutations in KCNQ1 are the most common cause of LQTS. Although rare, mutations in KCNQ1 also can cause familial AF. This report describes a child with a KCNQ1 missense mutation who uniquely expresses concomitant AF and LQTS. Due to the potential for increased morbidity and mortality, young patients who present with AF and a family history suggestive of inherited arrhythmias should trigger further investigation for LQTS and subsequent familial genetic counseling.